Pengaruh Pemasaran Produk Makanan dan Minuman Terhadap Minat Beli Konsumen : (Studi Kasus di Green Cafe 15 A Kota Metro) - I Putu Dananjaya Krisna (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Marketing cannot be separated from the marketing mix concept, which includes aspects of place, product, price and promotion. Green Cafe is one of the restaurants that implements a marketing mix strategy with the aim of attracting consumer buying interest. This marketing mix strategy is expected to support restaurant growth and ultimately increase revenue. This type of research is field research which has a correlational quantitative approach. This research aims to explore the cause-and-effect relationship between the independent variable and the dependent variable. The data collection method in this research involved unstructured interviews with Green Cafe employees and owners, distributing questionnaires to 67 respondents with a Likert scale, and documentation to complete the research data, including brochures and Green Cafe menu lists. The research results show that the t test produces a calculated t value that exceeds the t table value (2.597 > 2.000), so that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that the marketing variable (X) has a significant influence on consumer buying interest (Y). The marketing regression coefficient (X) of 0.431 indicates that the relationship is positive.